Experimental thermomechanic study of Newtonian and Non-Newtonian suspensions flows - GRADECK, Michel; FAGLA, FANOU ZINSOU BENOÎT; BARAVIAN, Christophe; LEBOUCHE, Michel (My University, 2005)
Hydrodynamic and thermal analysis of suspension flows is difficult but fundamental task for the sterilization problems of particles charged i food industries and also in any process where we can find flow with seeded particles. Nowadays the influence of solid suspended particles of the flow is not yet a well-known problem. Nevertheless, the solid particles have a strong influence on the rheological mixture's behavior. The new approach of these solid-liquid supension flows that we propose is based on experimental data and theorical considerations. We use hard sphere approach in order to model the pressure drop assuming the mixture as effective continuous medium.On these bases, we present a model of the heat transfer at the wall.
Keywords: Suspension Solid-Liquid; Rheology; Heat transfer